UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI MEMBANDINGKAN BILANGAN DENGAN MENGGUNAKAN MEDIA KARTU BILANGAN PADA SISWA KELAS II SDN 01 WINONGO SEMESTER 2 TAHUN PELAJARAN 2023/2024 - Nita Alfi Nur Rohmah; Choirijah, Choirijah Retnaningrum; Ibadullah, Ibadullah Malawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In learning activities, the use of learning media is an important part in delivering learning materials, one of which is the use of Number Card Media in Mathematics Learning for Class II SDN 01 Winongo Madiun. In general, the purpose of this study is to describe the improvement of student learning outcomes in Mathematics subjects with the use of number card media in class IIB SDN 01 Winongo Madiun with the material Comparing Numbers. The subjects of the study were class IIB students with a total of 28 students. This type of research is Classroom Action Research (CAR), which is carried out in two cycles, each cycle is carried out for 1 meeting. Both cycles consist of the planning, implementation, observation and reflection stages. The method used is quantitative descriptive, Data analysis techniques use individual completeness formulas and classical completeness. The criteria for the success of this research action is the percentage of classical completeness that reaches ≥ 75%. Data collection techniques in this study use observation and test techniques. The average student learning outcomes in the pre-cycle were 43%, cycle I was 46% and after the action it became 79% in cycle II with a minimum completion criterion of 70. This means that the use of number card media can improve the learning outcomes of Mathematics on the material of comparing numbers of class IIB students at SDN 01 Winongo Madiun.